Electromagnetic fields and waves near aperture antennas large electric dimensions - Горобец, Н. Н.; Овсянникова, Е. Е. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
Based on the solution of the exterior problem of electrodynamics of radiation aperture antennas in the near and intermediate zones are theoretically investigated the amplitude and phase characteristics of electromagnetic fields in the searchlight beam phase square aperture with a constant amplitude distribution of field sources. It is shown that in the searchlight beam is formed by a local non-uniform quasi-plane wave whose amplitude and power which changes in the distribution slightly up to a distance equal to a half the distance far field antenna. The spatial boundaries of the searchlight beam determined